Zbrodnia w fantastycznych światach - Trocha, Bogdan (1963- ) (Zielona Góra: Pracownia Mitopoetyki i Filozofii Literatury)
The main aim of the trial was to examine the mechanisms governing the use of fantasy motifs and criminal motives in literature. Due to the fact that criminal novels and fantasy literature belong to popular prose and because of the specificity of literary fantasy itself, it was necessary to define precisely the terms within which we could conduct research that interferes with us.For this reason, three models of understanding fantasy were adopted, which, according to the author, reflected the specificity of the literary material taken into account. Since the criminal motives present in the fantasy novels were not limited to a set of detective fantasy fantasy, it was necessary to apply a research methodology that would allow for the most precise understanding of this problem.
Keywords: fantastyka; kryminał; literatura; powieść; tematy i motywy; literaturoznawstwo